2017
DOI: 10.1097/wnp.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Revised Brain Symmetry Index, an EEG Feature Index, and Short-term Prognosis in Acute Ischemic Stroke

Abstract: The early prediction of functional outcomes after stroke may enhance clinical management and minimize short-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 12 publications
5
27
0
1
Order By: Relevance
“…Nevertheless, the comparisons of BSIs in the groups with different lesion sites and lesion side by an analysis of variance both showed no significant difference, and the same result can be found in a study in regard to BSI [24].…”
Section: B Effects Of the Lesion Stie And Lesion Sidesupporting
confidence: 77%
“…Nevertheless, the comparisons of BSIs in the groups with different lesion sites and lesion side by an analysis of variance both showed no significant difference, and the same result can be found in a study in regard to BSI [24].…”
Section: B Effects Of the Lesion Stie And Lesion Sidesupporting
confidence: 77%
“…In accordance with the data of X. Xin et al (2017) poor functional outcomes were associated with higher BSI [18]. Our research studied the prognostic value of interhemispheric different frequency bands asymmetry indexes, while independent association with the functional outcome of CISS acute period was only determined for IHRA of alpha band.…”
Section: Discussionsupporting
confidence: 74%
“…In the study of M. E. Wolf et al (2017), it was found that generalized (bilateral) changes of the bioelectric activity of the brain reflect the severity of supratentorial structures damage in patients with cerebral ischemic hemispheric stroke, not the focal ones [19]. The numerous studies demonstrate a high diagnostic informative value of the integral EEG pattern coefficients, which reflect the severity of slowwave activity within the assessment of the severity of acute brain damage of ischemic and traumatic genesis [2,4,5,17]. The conducted study allowed us to obtain data on reciprocal changes in the anterior and posterior gradient of EEG pattern rhythms in patients with SSICH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the overwhelming majority of scientific research related to the study of the functional state of cerebral structures within brain injuries of various origins with the use of spectral analysis of bioelectric activity of the brain was aimed at the determination of isolated parameters that are associated with clinical and neuroimaging data and the outcome of the disease [4,7,10,17]. Besides, it is necessary to mention that this monoparametric approach has restrictions, since the functional state of the brain in patients with brain damage in supratentorial localization is a very complex and extremely variable set of relied changes of absolute power, structure, zonal distribution of rhythms of different ranges in affected and intact hemispheres, as well as interhemispheric rhythm asymmetry [2].…”
Section: а а кузнецовmentioning
confidence: 99%